2015
DOI: 10.30935/scimath/9421
|View full text |Cite
|
Sign up to set email alerts
|

Animation model to conceptualize ATP generation: a mitochondrial oxidative phosphorylation

Abstract: Adenosine triphosphate (ATP) is the molecular unit of intracellular energy and it is the product of oxidative phosphorylation of cellular respiration uses in cellular processes. The study explores the growth of the misconception levels amongst the learners and evaluates the effectiveness of animation model over traditional methods. The data obtained from the sixty B.Sc. students found the growing misconception status in the mitochondrial oxidative phosphorylation test. Euclidean Distance Formula was used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The students ISSN 1648-3898 that chose the incorrect reason A may only have basic knowledge of chemiosmosis as a process to produce ATP; they did not understand the theory behind chemiosmosis and were not able to explain the concept of how energy is transferred or transformed in the production of ATP by chemiosmosis. This result is in line with research conducted by Jena (2014) who found that the growing misconception status of learners in ATP generation from mitochondrial oxidative phosphorylation is high.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The students ISSN 1648-3898 that chose the incorrect reason A may only have basic knowledge of chemiosmosis as a process to produce ATP; they did not understand the theory behind chemiosmosis and were not able to explain the concept of how energy is transferred or transformed in the production of ATP by chemiosmosis. This result is in line with research conducted by Jena (2014) who found that the growing misconception status of learners in ATP generation from mitochondrial oxidative phosphorylation is high.…”
Section: Discussionsupporting
confidence: 92%
“…According to researchers in this area (for e.g. Bajd, Praprotnik and Matyasek, 2010;Jena, 2014) cellular respiration topic is very difficult to understand.…”
Section: Discussionmentioning
confidence: 99%
“…Multimedia and its components. As misconceptions and difficulties among college students abound regarding cardiorespiratory physiology, and oxidative phosphorylation and ATP generation by mitochondria (10,16,18), together with an inability to integrate relevant science knowledge (7,14), a multimedia instruction package for undergraduate nursing students was developed. The multimedia package was created with a focus on correcting the misconceptions and reducing the barrier to attain basic science knowledge required for proper understanding of BLS.…”
Section: Participantsmentioning
confidence: 99%
“…A recent study involving healthcare providers in the U.S. reported students are unable to answer questions on basic human physiology and on reasons for performing chest compression (7). A clear comprehension on oxidative phosphorylation and adenosine triphosphate (ATP) generation by mitochondria prove difficult according to a study of undergraduate students at a university in India (10).…”
Section: Introductionmentioning
confidence: 99%